Disadvantage in English seaside resorts: A typology of deprived neighbourhoods. (December 2018) - Agarwal, Sheela; Jakes, Steven; Essex, Stephen; Page, Stephen J.; Mowforth, Martin
Abstract: Socio-economic disadvantage experienced by residents of English seaside resorts has been growing over the last decade, and academic and practice-based research is providing better insights into the causes, internal dynamics and appropriate policy responses to these issues in coastal communities. This paper examines the nature and extent of disadvantage in English seaside resorts through analysis of a specially devised spatial and temporal database, which draws together various publicly available sources beyond the population census and Index of Multiple Deprivation. Using univariate, bivariate and multivariate analyses of this database, a new typology of highly deprived resort neighbourhoods has been devised, with clear implications for the formulation of more targeted policy responses. The results also indicate the persistence, complexity and distinct spatial clustering of deprivation, which establishes a case for a much stronger geographical emphasis in future research and policy agendas, including third sector partnerships. Highlights: Documents insights gained from a new spatial and temporal seaside resort database about disadvantage. Deprivation in seaside resorts is shown to be persist, complex and with distinct spatial clustering. On the basis of this data, a new typology of highly deprived resorts areas has been formulated. Demonstrates the relationship between disadvantage, multiple deprivation and social exclusion. Establishes a case for a stronger geographical emphasis in future research and policy agendas.